Alcohol consumption and risky traffic behaviors among university students (Research, Society and Development, 2020)
The aim of this study was to analyze the factors associated with risky behavior related to alcohol consumption in university students. This is a cross-sectional study carried out with students from a public university in the interior of Bahia in the period of 2019. Descriptive and associated factor analyzes were performed using chi-square tests, student's t and Logistic Regression with estimation of odds ratio (OR). 276 undergraduate students with an average age of 23 years participated in this study, 74.6% women, and 89.1% singles. Alcohol consumption was reported by 56.5% of university students. Male students were more prevalent in the behavior of being a passenger in a vehicle driven by someone under the influence of alcohol (82.9%), in addition to being 11.55 times more likely to drive a motorcycle or car after taking three or more doses of alcohol (95% CI 2.86 - 46.58). Driving a motor vehicle after ingesting any amount of alcoholic beverage is associated with the type of user (except pedestrian) (p